Pseudopyricularia hedjaroudii sp. nov. (Pyriculariaceae, Magnaporthales): a novel species from Iran - Ghorbani, Golzar; Pordel, Adel; Javan-Nikkhah, Mohammad (Phytotaxa, 2021)
In a survey of pyricularia-like fungi on different plants, especially on sedges in the north of Iran, we identified two typical isolates characteristics of the genus Pseudopyricularia. Phylogeny analysis based on DNA sequences of internal transcribed spacer regions (ITS-rDNA), the largest subunit of the RNA polymerase II (RPB1), calmodulin (CAL), and large subunit of the ribosomal RNA (LSU) gene regions, and morphological criteria confirmed the new species of Pseudopyricularia. Pseudopyricularia hedjaroudii sp. nov., isolated from the leaves of Cyperus sp., is described and illustrated. Conidia of the Ps. hedjaroudii are obclavate, obpyriform, and 1-septate distinct from other allied species in size and shape.